Anisotropy as an indicator for reservoir changes: example from the Rotokawa and Ngatamariki geothermal fields, New Zealand. Issue 1 (5th September 2019) - Mroczek, Stefan; Savage, Martha K; Hopp, Chet; Sewell, Steven M
SUMMARY: We investigate the relation between geothermal field production and fracture density and orientation in the Ngatamariki and Rotokawa geothermal fields, located in the Taupo Volcanic Zone, New Zealand using shear wave splitting (SWS). We determine the SWS parameters for 17 702 microseismic events across 38 stations spanning close to 4 yr from 2012 to 2015. We compare the strength of anisotropy to changes in field production and injection. We also compare the orientation of the anisotropy to in situ and regional measurements of maximum horizontal stress orientation. (S_ H_ max ). Due to the volume of unique events (approximately 160 000), shear wave phases are picked automatically. We carry out automatic SWS measurements using the Multiple Filter Automatic Splitting Technique (MFAST). The SWS measurements are interpreted in the context of stress aligned microcracks. Outside both fields and within Ngatamariki, fast polarizations align with the NE–SW regional orientation of S_ H_ . Within Rotokawa a greater complexity is observed, with polarizations tending toward N–S. We observe increases in per cent anisotropy coinciding with the start of production/injection in Ngatamariki and then a later correlated drop in per cent anisotropy and v P / v S ratios in southern Ngatamariki as injection is shifted to the north. This relationship is consistent with pore fluid pressure within the reservoir being affected by local changes in production and injection of geothermal fluids causing cracks to open and close in response.